A Roughness Model Implementation to Analyze Sound Mass Composition: A Case Study in Ligeti’s Continuum for Harpsichord (1968) - Antunes, Micael; Espírito Santo, Guilherme Feulo do; Manzolli, Jônatas (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2021: Anais do XVIII Simpósio Brasileiro de Computação MusicalDO - 10.5753/sbcm.2021.19430, 2021)
We present in this paper an implementation of a roughness descriptor based on the model of Pantelis Vassilakis. We apply the implemented descriptor to perform a computer-aided musical analysis of György Ligeti’s Continuum for harpsichord (1968). Our analysis establishes a parallel between the roughness model, concepts of sound mass composition, and Ligeti’s ideas of timbre of movement and permeability. As a result, we display a graphical representation for the roughness present in the Continuum’s recording, propose a formal segmentation for the piece, and analyze its formal development from a musicological point of view.